Management of Retinopathy of Prematurity in an African Population- An Analytical Retrospective Comparative Study (Global Journal of Medical Research, 2022)
Retinopathy of prematurity ROP is common cause of blindness if not properly diagnosed and promptly managed Treatment modalities used are indirect laser ophthalmoscopy ILO intravitreal anti-vascular endothelial growth factors injection monotherapy IAVEGFIM and Retinal Detachment Surgery RDS
Keywords: retinal neovascularization; prematurity; childhood blindness; low birth weight; neonatal oxygen therapy